2013
DOI: 10.1016/j.mce.2013.02.017
|View full text |Cite
|
Sign up to set email alerts
|

The ERK1/2 pathway regulates testosterone synthesis by coordinately regulating the expression of steroidogenic genes in Leydig cells

Abstract: Adult mice with a Leydig cell specific deletion of MAPK kinase (MEK) 1 and 2 (Mek1f/f;Mek2−/−;Cre+) mice display Leydig cell hypoplasia and hypergonadotropic hypogonadism. We used radioimmunoassays and quantitative PCR to evaluate the function and expression of the Leydig cell genes involved in the conversion of cholesterol to testosterone (Star, Cyp11a1, Hsd3b6, Cyp17a1 and Hsd17b3), androgen metabolism (Srda1 and Dhrs9), and four transcription factors (Creb1, Nr5a1, Nr4a1 and Nr0b1) that regulate the express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 49 publications
0
27
0
Order By: Relevance
“…Results from the gene expression analysis corroborate the pCreb activation pattern, since no different increase of LH- and hCG-induced Stard1 gene expression levels were observed. Indeed, in murine Leydig cells, Stard1 gene expression occurs as a pCreb-dependent event [13], although several other modulators of the steroidogenic response were described [43]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Results from the gene expression analysis corroborate the pCreb activation pattern, since no different increase of LH- and hCG-induced Stard1 gene expression levels were observed. Indeed, in murine Leydig cells, Stard1 gene expression occurs as a pCreb-dependent event [13], although several other modulators of the steroidogenic response were described [43]. …”
Section: Discussionmentioning
confidence: 99%
“…Hormone binding to LHCGR triggers the activation of adenylyl cyclase through Gαs protein, resulting in intracellular cyclic adenosine-monophosphate (cAMP) increase, in downstream activation of the protein kinase A (PKA) [11, 12] which, in turn, induces extracellular signal-regulated kinases 1 and 2 (ERK1/2) phosphorylation [13]. PKA also mediates the activation of the cAMP-response element-binding protein (CREB), modulating the expression of target genes, such as the steroidogenic acute regulatory protein ( STARD1 ) gene, and testosterone production.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Testosterone production by Leydig cells is regulated by complex interplay between multiple molecules including those involved in endocrine and paracrine signaling, and proper regulation is critical for optimum reproductive capacity. As a result, a number of Leydig cell-specific genes have been identified as important regulators of reproductive processes (26)(27)(28)(29)(30). As PLP-J is specifically expressed in Leydig cells of the testis and its expression peaks in the adult, similar to the expression pattern of testosterone, we hypothesized that PLP-J is also involved in testosterone biogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…It was later reported that activation of LHCGR leads to a transient cAMP-dependent activation of the EGFR and downstream mitogen-activated protein kinase (MAPK) cascade [75]. The involvement of the MAP kinases extracellular signal-regulated kinases 1 and 2 (ERK1/2) downstream of PKA have long been known to be essential for proper LH-induced steroidogenesis in Leydig cells [76][77][78][79][80][81][82] (Fig. 1).…”
Section: Intracellular Signaling Pathwaysmentioning
confidence: 99%